METODOLOGI KRITIK TAFSIR (Konsep Dasar, Akar Filosofis, Historis Dan Perkembangan Metodologis) - Fauzan Sugiyono; Muhammad Ismail (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
This study investigates the necessity of critical evaluation in Qur’anic interpretation, prompted by the existence of various exegetical approaches that deviate from established hermeneutical principles. It offers a comprehensive examination of the concept, philosophical underpinnings, and historical trajectory of tafsir criticism. Methodologically, tafsir critique serves as a tool for identifying, scrutinizing, and correcting interpretive methods to ensure their coherence with Islamic epistemology and values. Employing a qualitative framework with historical and descriptive analysis, this research traces the evolution of interpretive critique from the classical to the contemporary era. The findings reveal that tafsir criticism extends beyond textual analysis, integrating contextual, linguistic, and epistemological considerations. Historically, its roots can be traced back to the era of the Prophet’s Companions and the Tabi‘in, later expanding through the development of sanad-based critique in riw?yah tafsir and hermeneutical methodologies in modern exegesis.